Bootstrapped Monte Carlo spline and confidence interval generation for ice core gas records in: 'Reconciling ice core CO2 and land-use change following New World-Old World contact' ... - King, Amy (Zenodo, 2023)
Bootstrapped Monte Carlo spline and confidence interval generation for ice core gas records in: 'Reconciling ice core CO2 and land-use change following New World-Old World contact'. ...